IMPACT OF PRINCIPAL`S INSTRUCTIONAL LEADERSHIP ON TEACHER EFFICACY AT SECONDARY SCHOOL LEVELS IN KHYBER PAKHTUNKHWA - Inam Ullah; Dr. Rahim Khan (`, 2025)
The research explores the connection among the variables, the independent variable instructional or pedagogical leadership and the dependent variable teacher self-efficacy (teacher self-confidence), alongside assessing the validity and reliability of the variables in the government sector high secondary schools within the four districts of the province Khyber Pakhtunkhwa, Pakistan. Specifically, the research investigates the influence of independent variable instructional leadership on the dependent variable teacher self-efficacy. Employing a quantitative approach, two questionnaires, the IMRS and TSE scales, were utilized for data collection. The snowball sampling method was put to use in a sample of 523 participants comprising 189 principals and 334 teachers. The statistical analysis of the population confirms the resemblance. The outcomes reveal that the independent variable instructional leadership has notable influences on the dependent variable teacher self-efficacy, boosting an environment conducive to constructive feedback on predefined goals. This, in turn, permits teachers to develop and sustain a great level of self-efficacy. The study highlights the essential role of principals in boosting teacher self -abilities. These outcomes have notable implications for school administrators, policy-makers, and educators, providing a foundation for effective leadership enhancement programs and institution improvement drives aimed at elevating instructional quality. Finally, this research underscores the significance of student learning attainments and overall educational quality, which in innately linked to instructional leadership. Key words: leadership, instructions, Efficacy.